Fast TiO2 Sensitization Using the Semisquaric Acid as Anchoring Group. (7th November 2013) - Pugliese, D.; Shahzad, N.; Sacco, A.; Musso, G.; Lamberti, A.; Caputo, G.; Tresso, E.; Bianco, S.; Pirri, C. F.
Abstract : Metal-free dye molecules for dye-sensitized solar cells application can avoid some of the typical drawbacks of common metal-based sensitizers, that are high production costs, relatively low molar extinction coefficient in the visible region, limited availability of precursors, and waste disposal issues. Recently we have proposed an innovative organic dye based on a simple hemi-squaraine molecule (CT1). In the present work, the effect of the sensitization time of the TiO2 photoelectrode in the dye solution is studied with the aim of optimizing the performance of CT1-based DSCs. Moreover, the addition of the chenodeoxycholic acid (CDCA) as coadsorbent in the dye solution at different concentrations is investigated. Both CT1-sensitized mesoporous TiO2 photoanodes and complete solar cells have been fully characterized in their electrical and absorption properties. We have found that the best photoconversion performances are obtained with 1 hour of impregnation time and a 1 mM CDCA concentration. The very fast kinetics in dye adsorption, with optimal sensitization steps almost 15 times faster than conventional Ru-based sensitizers, confirms the theoretical predictions and indicates a strong interaction of the semisquaric acid group with the anatase surface. This result suggests that this small molecule can be a promising sensitizer even in a continuous industrial process.